Design technique for leakage current reduction in surge arrester using gravitational search algorithm and imperialist competitive algorithm. Issue 1 (2nd January 2018) - Abdul Latiff, Nurul Ain; Illias, Hazlee Azil; Abu Bakar, Ab Halim; Abd Halim, Syahirah; Dabbak, Sameh Ziad
Abstract : Purpose: Leakage current is one of the factors, which can contribute towards degradation of surge arresters. Thus, the purpose of this paper is to study on leakage current within surge arresters and improvement on their design. Design/methodology/approach: In this work, a three-dimensional model geometry of 11 kV zinc oxide surge arrester was designed in finite element analysis and was applied to calculate the leakage current under normal operating condition and being verified with measurement results. The optimisation methods were used to improve the arrester design by minimising the leakage current across the arrester using imperialist competitive algorithm (ICA) and gravitational search algorithm (GSA). Findings: The arrester design in reducing leakage current was successfully optimised by varying the glass permittivity, silicone rubber permittivity and the width of the ground terminal of the surge arrester. It was found that the surge arrester design obtained using ICA has lower leakage current than GSA and the original design of the surge arrester. Practical implications: The comparison between measurement and simulation enables factors that affect the mechanism of leakage current in surge arresters to be identified and provides the ideal design of arrester. Originality/value: Surge arrester design was optimised by ICA and GSA, which has never been applied in past works in designing surge arrester with minimum leakage current.